Diagnóstico organizacional através de ferramentas da qualidade: um estudo de caso em uma empresa atacadista - Holanda, Yêda Lessandra (Universidade Federal Rural do Semi-Árido, 2020)
The market is increasingly competitive in search of quality at low costs. To adapt to this scenario, continuous improvements in organizations are required. An increasingly used way for this is the application of quality tools. Thus, the aim of this study is to perform an organizational diagnosis of a wholesale company through quality tools. To achieve the aim of this case study, a descriptive applied research was carried out, having as data collection semi- structured interviews applied with collaborators of the studied organization. The results were presented through the sequential use of four tools: Brainstorming, GUT Matrix, Cause and Effect Diagram and 5W3H. Three solutions were proposed for the improvement of the studied organization. It is concluded that the study contributed in a practical way to the organization management, as well as presented important elements for the academic development of the theme
Monografia
Keywords: Gestão da qualidade; Ferramentas da qualidade; Melhoria contínua; Quality management; Quality tools; Continuos improvement; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO